A novel in vitro method to detect inhibitors of protein glycation - HKI Perera (Asian Journal of Medical Sciences, 2014)
Background: Protein glycation generates advanced glycation end products (AGEs) which are implicated in the pathogenesis of chronic complications associated with diabetes. Identifi cation of medicinal plants with protein glycation inhibitory potential will enhance the opportunity to delay or inhibit diabetic complications with minimum side effects. Techniques available to identify protein glycation inhibitors require expensive specialized equipment.